2019
DOI: 10.1155/2019/8575398
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants as Renoprotective Agents for Ischemia during Partial Nephrectomy

Abstract: Small renal masses have been diagnosed increasingly in recent decades, allowing surgical treatment by partial nephrectomy. This treatment option is associated with better renal function preservation, in comparison with radical nephrectomy. However, for obtaining a bloodless field during surgery, occlusion of renal artery and veins is often required, which results in transitory ischemia. The renal ischemia-reperfusion injury is associated with increased reactive oxygen species production leading to renal tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 107 publications
0
29
0
Order By: Relevance
“…Although the pathophysiological mechanisms underlying I/R injury are not fully understood, the excessive oxidative stress is a key initiator of I/R injury. Reactive oxygen species overload can overwhelm the intracellular antioxidant system, leading to apoptosis and tissue damage [35,36]. Several publications revealed that miR-153 is involved in the regulation of oxidative stress response through modulation of Nrf2 in bovine granulosa cells [37], breast cancer cells [38], and neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathophysiological mechanisms underlying I/R injury are not fully understood, the excessive oxidative stress is a key initiator of I/R injury. Reactive oxygen species overload can overwhelm the intracellular antioxidant system, leading to apoptosis and tissue damage [35,36]. Several publications revealed that miR-153 is involved in the regulation of oxidative stress response through modulation of Nrf2 in bovine granulosa cells [37], breast cancer cells [38], and neurons.…”
Section: Discussionmentioning
confidence: 99%
“…ROS levels are increased in ischemic kidney injury and are a key driver of cellular injury (Ratliff et al 2016). Buys-Gonçalves et al (2019) reported the pathophysiological role of free radicals in ischemic kidney injury. By contrast, cellular antioxidants such as catalase, SOD, and GPx prevent the detrimental effects of free radicals generated by ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia-mediated AKI results from a generalized or localized impairment of oxygen and nutrient delivery to, and waste product removal from, the cells of the kidney [52]. There is a mismatch of local tissue oxygen supply and demand and accumulation of waste products of metabolism.…”
Section: Pathophysiology Of Akimentioning
confidence: 99%
“…Several studies have unambiguously demonstrated that endocannabinoids modulate proliferation and apoptosis of T and B lymphocytes, macrophage-mediated killing, cytokine production, immune cell activation by inflammatory stimuli, chemotaxis and inflammatory cell migration [52,53]. Most if not all of these effects have been reported to be primarily mediated via CB2 receptors causing inhibition of the cAMP/protein kinase A pathway.…”
Section: Protection Against I/r-injurymentioning
confidence: 99%
See 1 more Smart Citation